Ketidakpatuhan Masyarakat terhadap Peraturan Daerah Tentang Kawasan Tanpa Rokok Di Rumah Sakit Universitas Hasanuddin - Achmad Mawardi Shabir; Rusda Ananda; Rizky Maharja; Andi Mifta Farid Panggeleng (KOLONI, 2023)
The policy to implement the smoke-free area (KTR) in hospitals has long been an intervention strategy to control non-communicable diseases. Regulations in the form of regional regulations on smoke-free area (KTR) are also agreed in various countries as an embodiment of tobacco regulations in the world. Implementation of regional policies issued must be carried out by all Local Governments in Indonesia. This study discusses influential factors related to the community in the smoke-free area at Hasanuddin University Hospital. This research is a type of quantitative research using cross-sectional study. The population in this study was 100 people. Sampling was carried out using a non-probability sampling method with convenience sampling technique so that a total sample of 100 people was obtained. Processing and analysis of data using the SPSS program. Data analysis was based on the Chi-Square Test statistic. The results showed there was a relationship between understanding of instructions (p = 0.023), there was a relationship between beliefs (p = 0.006), there was a relationship between attitudes (p = 0,000) and self-control (p = 0,000) with community non-compliance with regional regulations on the area without cigarettes at Hasanuddin University Hospital. The results of multiple logistic regression tests were simultaneously obtained that attitudes (Exp. B = 10.670) and self-control (Exp. B = 5.394) were the most influential variables on community non-compliance at Hasanuddin University Hospital. 023), there is a relationship between belief (p = 0.006), there is a relationship between attitude (p = 0,000) and self-control (p = 0,000) with community non-compliance with local regulations on smoke-free area in Hasanuddin University Hospital. The results of multiple logistic regression tests were simultaneously obtained that attitudes (Exp. B = 10.670) and self-control (Exp. B = 5.394) were the most influential variables on community disobedience at Hasanuddin University Hospital. 023), there is a relationship between belief (p = 0.006), there is a relationship between attitude (p = 0,000) and self-control (p = 0,000) with community non-compliance with local regulations on smoke-free area in Hasanuddin University Hospital. The results of multiple logistic regression tests were simultaneously obtained that attitudes (Exp. B = 10.670) and self-control (Exp. B = 5.394) were the most influential variables on community non-compliance at Hasanuddin University Hospital. Keywords: Non-compliance, KTR, hospitals, policies, regional regulations